Stages of Organic Matter Addition vs. N Transformation in Soil - Paul, Niladri; Chakraborty, Jayeeta; Saha, Dipankar; Chakraborty, Rajib Ranjan; Das, Saradindu (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
FYM and mustard cake, the two variable source of organic matter, were used as amendments and N sources in a typic ustifluvent soil. Organic matters were added at two modes i.e 21 days before and on the day of actual start of the experiment. Inorganic N as urea was added as treatment material. Results of the experiment reveal that comparatively higher amount of inorganic N was accumulated in soil incubated at 21 days compared to soils amended with organic matter upto 90 days period. Compared to the sources of organic matters, it was observed that the amount of inorganic N was recorded much higher in mustard cake amended soil than that of the soil amended with FYM. However, the amount of organic N content did not vary much and also did not show any definite trend of changes. The overall result showed that mustard cake proved superior results over that of FYM with regard to accumulation of inorganic N in soil. Addition of organic matters 21 days before the start of the experiment showed better results with regards to availability of N in soils.